Treatment of Gingival Fenestration using Mucoperiosteal Flap with Connective Tissue Graft: A Report of Two Cases - Jaglan, Swati; Tewari, Shikha (Journal of Dentistry Indonesia, 2023)
Fenestration term is derived from the Latin word ‘fenestra’ means ‘window’. Gingival fenestration is not found in routine while its actual occurrence is assumed to be higher. Additionally, if these mucogingival defects persist for a longer duration it may lead to adverse outcomes like compromised esthetics, hypersensitivity, plaque and calculus deposition, and susceptibility to dental caries. Present cases of gingival fenestration were successfully treated by using full-thickness flap elevation with connective tissue graft placement. Two cases were presented with the accumulation of plaque and calculus and having gingival fenestration to the respective sites. After phase 1 therapy, full thickness flap was raised and a connective tissue graft was placed beneath the fenestrated area. The successful results were obtained in both cases in terms of complete closure of gingival fenestration defects and well-adapted margins with adjacent tissues at one year of follow-up. Full thickness flap with connective tissue graft procedure resulted in complete closure of gingival fenestration in both cases with no recurrence at one-year follow-up and can be used as a successful and predictable treatment modality for the management of such cases.